DEVELOPMENT OF DATA ACQUISITION SYSTEM FOR MOBILE ULTRAVIOLET (UV) MONITORING DEVICE - Muhammad Hafizuddin; Muhammad Danish Shukor; Mohd Firdaus Malek; Ruziana Mohamed; Azlin Haezrina Kamarzaman; Marmeezee Mohd Yusoff; Mohd Asyraf Mohd Razib; Nurul Sakinah Engliman (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
In this age of modernization, smart or self-sufficient frameworks in all domains of work are becoming increasingly important as innovation advances. This involves improving data collecting for UV monitoring system using metal oxide sensors, an underdeveloped market niche. The Data Acquisition (DAQ) system available at the moment is antiquated and frustrating. This project aims to establish a framework for acquiring information about UV monitoring devices using metal oxide sensors. Metal oxide-based sensor uses titanium dioxide nanorod arrays (TNAs). Self-powered UV photosensor creates electricity when exposed to UV light. UV photosensors are photoelectrochemical (PEC). Monitoring the sensor’s real-time output voltage in relation to UV intensity evaluates the data acquisition system’s performance. A Raspberry Pi is used to evaluate the data security architecture for the Cytron-UNO development board. The sensor’s data gathering system detected the current produced and stamped the date and time on it. This paper discusses trait formation and experimental data.